The World as a Mathematical Game John von Neumann and Twentieth Century Science - Israel, Giorgio; Millán Gasca, Ana (Science Networks. Historical Studies,, 2009)
Galileo and Newton's work towards the mathematisation of the physical world; Leibniz's universal logical calculus; the Enlightenment's mathématique sociale. John von Neumann inherited all these aims and philosophical intuitions, together with an idea that grew up around the Vienna Circle of an ethics in the form of an exact science capable of guiding individuals to make correct decisions. With the help of his boundless mathematical capacity, von Neumann developed a conception of the world as a mathematical game, a world globally governed by a universal logic in which individual consciousness moved following different strategies: his vision guided him from set theory to quantum mechanics, to economics and to his theory of automata (anticipating artificial intelligence and cognitive science). Von Neumann became a true legend in twentieth century science; but he was also a controversial figure, because of the decisive role he played in determining US military policy and strategic atomic equilibrium - which he viewed as an application of game theory. The Cold War is over; the age of nuclear physics and big science has been superseded by our age of biotechnology and postacademic science. From the life of John von Neumann emerge important insights to understand the cultural and technological landscape that we have inherited from the past century. This book provides the first comprehensive scientific and intellectual biography of John von Neumann, a man who perhaps more than any other is representative of twentieth century science. There are hundreds of metaphors for life: Life is a vale of tears, a dream, a joke. In As You Like It, Shakespeare says that life is a stage. What was von Neumann's metaphor? [...] it was that life is a game. Sensitive to the double-edged sword of knowledge and the idiocy of mankind, von Neumann's main legacy might be the deepening of the ancient dilemma of Prometheus. (Philip Davis, Siam News, May 30, 2003).